Effectiveness of a booster dose of COVID-19 vaccines during an outbreak of SARS-CoV-2 Omicron BA.2.2 in China: A case–control study. Issue 1 (31st December 2023) - Zhang, Xiaqing; Wang, Yao; Hu, Chengyang; Xu, Pengpeng; Ma, Liguo; Liu, Lei; Sun, Jie; Liu, Yang; Yang, Hui; Pan, Fan; Hu, Jieying; Cao, Chengsong; et al.
ABSTRACT: Real-world evidence on the effectiveness of COVID-19 vaccines marketed in China against the Omicron BA.2.2 variant remains scarce. A case–control study was conducted to estimate the vaccine effectiveness (VE) of COVID-19 vaccines marketed in China (inactivated vaccines, an Ad5-nCoV vaccine, and a recombinant protein vaccine). There were 414 cases infected with SARS-CoV-2 and 828 close contacts whose test results were consecutively negative as controls during the outbreak of the Omicron variant in Lu'an City, Anhui Province, China, in April 2022. The overall adjusted VE against Omicron BA.2.2 variant infection in the vaccinated group with any COVID-19 vaccine was 35.0% (95% CI: −9.1–61.3%), whereas the adjusted VE for booster vaccination was 51.6% (95% CI: 15.2–72.4%). Subgroup analysis showed that the overall adjusted VE of the Ad5-nCoV vaccine (65.8%, 95% CI: 12.8–86.6%) during the outbreak while any dose of inactivated vaccines and recombinant protein vaccine offered no protection. The adjusted VE of three-dose inactivated vaccines was 48.0% (95% CI: 8.0–70.6%), and the two-dose Ad5-nCoV vaccine was 62.9% (95% CI: 1.8–86%). There is no protection from a three-dose recombinant protein vaccine. COVID-19 vaccines offered 46.8% (95% CI: 9.5–68.7%) protection from infection within six months. There were statistically significant differences between the VEs of heterologous booster (VE = 76.4%, 95% CI: 14.3–93.5%) and homologous booster vaccination (VE = 51.8%, 95% CI: 9.6–74.3%) ( P = .036). Booster vaccination of COVID-19 vaccines offered more protection than full vaccination. A booster vaccination campaign for a booster dose after three doses of a recombinant protein vaccine must be urgently conducted.